Characterization of Variants in the Glucosylceramide Synthase Gene and their Association with Type 1 Gaucher Disease Severity. Issue 10 (13th August 2013) - Alfonso, Pilar; Navascués, Joaquín; Navarro, Silvia; Medina, Pilar; Bolado‐Carrancio, Alfonso; Andreu, Vanesa; Irún, Pilar; Rodríguez‐Rey, José Carlos; Pocoví, Miguel; España, Francisco; Giraldo, Pilar
<x xml:space="preserve">Abstract</x> We examined glucosylceramide synthase gene (UGCG) polymorphisms and their correlation with Gaucher disease (GD) severity to explain the variability. Heterozygous [N370S]+[L444P] patients with c.[‐232_‐241ins10 (+) 98++++50G] haplotype had a significantly lower disease severity scoring system (DS3) score in relation to patients carrying only one of these polymorphisms. Luciferase reporter assays showed that [c.‐232_‐241ins10;98+50A], [c.‐232nonins;98+50G] and [c.‐232_‐241ins10;98+50G] haplotypes significantly reduced promoter activity. In conclusion, the c.‐232_‐241ins10 and c.98+50A>G variants are modifying factors of GD severity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>